Mediastinal staging by videomediastinoscopy in clinical N1 non-small cell lung cancer: a prospective multicentre study. Issue 6 (21st December 2017) - Decaluwé, Herbert; Dooms, Christophe; D'Journo, Xavier Benoit; Call, Sergi; Sanchez, David; Haager, Benedikt; Beelen, Roel; Kara, Volkan; Klikovits, Thomas; Aigner, Clemens; Tournoy, Kurt; Zahin, Mahmood; et al.
A quarter of patients with clinical N1 (cN1) non-small cell lung cancer (NSCLC) based on positron emission tomography–computed tomography (PET-CT) imaging have occult mediastinal nodal involvement (N2 disease). In a prospective study, endosonography alone had an unsatisfactory sensitivity (38%) in detecting N2 disease. The current prospective multicentre trial investigated the sensitivity of preoperative mediastinal staging by video-assisted mediastinoscopy (VAM) or VAM-lymphadenectomy (VAMLA). Consecutive patients with operable and resectable (suspected) NSCLC and cN1 after PET-CT imaging underwent VAM(LA). The primary study outcome was sensitivity to detect N2 disease. Secondary endpoints were the prevalence of N2 disease, negative predictive value (NPV) and accuracy of VAM(LA). Out of 105 patients with cN1 on imaging, 26% eventually developed N2 disease. Invasive mediastinal staging with VAM(LA) had a sensitivity of 73% to detect N2 disease. The NPV was 92% and accuracy 93%. Median number of assessed lymph node stations during VAM(LA) was 4 (IQR 3–5), and in 96%, at least three stations were assessed. VAM(LA) has a satisfactory sensitivity of 73% to detect mediastinal nodal disease in cN1 lung cancer, and could be the technique of choice for pre-resection mediastinal lymph node assessment in this patient group with a one in four chance of occult-positive mediastinal nodes after negative PET-CT. Videomediastinoscopy reaches a sensitivity of 73% detecting N2 disease in cN1 NSCLC patients; N2 prevalence is 26% http://ow.ly/VrzL30gIOWm